2008
DOI: 10.1121/1.2904826
|View full text |Cite
|
Sign up to set email alerts
|

Spatial release from energetic and informational masking in a selective speech identification task

Abstract: A masker can reduce target intelligibility both by interfering with the target's peripheral representation ("energetic masking") and/or by causing more central interference ("informational masking"). Intelligibility generally improves with increasing spatial separation between two sources, an effect known as spatial release from masking (SRM). Here, SRM was measured using two concurrent sine-vocoded talkers. Target and masker were each composed of eight different narrowbands of speech (with little spectral ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 64 publications
6
81
1
Order By: Relevance
“…A useful distinction can be made between those aspects of informational masking that cause difficulty in auditory object formation and those that cause difficulty in object selection (e.g., Ihlefeld and Shinn-Cunningham 2008). Consistent with this distinction, Roberts et al (2010) suggested that competitor formants reduce intelligibility because listeners are unable to reject them completely from the auditory perceptual organization of the sentence, which for optimum intelligibility should include only F1+F2+ F3.…”
Section: Informational Masking Of Speechmentioning
confidence: 94%
“…A useful distinction can be made between those aspects of informational masking that cause difficulty in auditory object formation and those that cause difficulty in object selection (e.g., Ihlefeld and Shinn-Cunningham 2008). Consistent with this distinction, Roberts et al (2010) suggested that competitor formants reduce intelligibility because listeners are unable to reject them completely from the auditory perceptual organization of the sentence, which for optimum intelligibility should include only F1+F2+ F3.…”
Section: Informational Masking Of Speechmentioning
confidence: 94%
“…There are 2 major, but not necessarily exclusive, categories of masking: energetic masking and informational masking (Ihlefeld & Shinn-Cunningham 2008, Yost et al 2008. Traditional energetic masking refers to the case when the masking sound contains energy in the same frequency band and occurs at the same time as the signal of interest, such that the signal is inaudible.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, ITDs and other spatial cues could benefit performance in a segregation task either by facilitating the segregation of a target source from background sources, or by making it easier to focus attention on the "correct" source amongst sources that are already well segregated Shinn-Cunningham, 2005;Ihlefeld et al, 2007;Shinn-Cunningham, 2008). Many of the previously documented benefits of spatial cues on understanding speech in sound mixtures likely derive from their influence on object selection.…”
Section: Discussionmentioning
confidence: 99%
“…In realistic listening situations, such as when attending to a particular speaker in a "cocktail party" environment, spatial cues indeed appear to aid segregation, improving the comprehension of target sentences in a background of other speakers (Bronkhorst, 2000;Drullman and Bronkhorst, 2000;Freyman et al, 2001;Hawley et al, 2004;Ihlefeld and Shinn-Cunningham, 2007). There are a few ways in which spatial cues could aid a listener in this situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation